Tourists’ perspectives on hard and soft services toward rural tourism destination competitiveness: Community support as a moderator - Lo, M.-C.; Chin, C.-H.; Law, F.-Y. (SAGE Publications Inc., 2019)
Rural tourism is an integrated part in the services field, and this industry has long been recognized as a valuable tool for economic development in rural destinations. However, the multiplying growth of rural tourism destinations has led to a stiff competition among the industry. Thus, the identification of tourists’ perspective on the hard and soft services components toward the development of rural tourism is a key element in surviving into the rapid tourism competition. The pivotal role of community support as an integral part of tourism product in ensuring sustainable development of rural tourism destination would also being the key indicator for the development of rural tourism. Hence, this study highlighted the importance of tourists’ perspective on hard services (tourism infrastructure and accommodation) and soft services (range of activities and special events) toward the competitiveness of rural tourism destination’s development with community support who act as a moderator. A total of 314 respondents comprising tourists who visited Kampung Semadang, Kampung Telaga Air, and Kubah National Park (Kampung Matang), Kuching, Sarawak has voluntarily participated in this study. To assess the developed model, SmartPLS 2.0 (M3) is applied based on path modeling and bootstrapping. Interestingly, the findings revealed that tourists are more concerned about the quality of accommodation, infrastructure, range of activities, and special events for the development of tourism destination competitiveness in rural tourism destination. In addition, tourists also believed that the existence of community support is crucial in moderating the relationship between accommodation quality and tourism destination competitiveness. This study further discussed on the implications of the findings, limitations, and directions for future research.